Data-Independent Acquisition Method for In-Depth Proteomic Screening of Donkey Meat - Liyuan Wang; Honglei Qu; Xinrui Wang; Tianqi Wang; Qiugang Ma; Muhammad Zahoor Khan; Mingxia Zhu; Changfa Wang; Wenqiang Liu; Wenqiong Chai (Agriculture, 2024)
Donkey meat has gained popularity as an emerging meat product due to its superior nutritional value and distinctive flavor. Despite this, research on the molecular mechanisms that contribute to meat quality, particularly within the field of proteomics, remains limited. This study aimed to address this gap by utilizing the data-independent acquisition (DIA) technique to identify differentially expressed proteins (DEPs) in the gluteus superficialis (WG), longissimus thoracis (WLT), and semitendinosus (WS) muscles of donkeys. Our analysis revealed 189 and 384 DEPs in the WG/WLT and WS/WLT muscles, respectively. Several significant potential pathways, involving these DEPs, were found to be closely associated with donkey meat quality. These pathways include fatty acid biosynthesis, TGF-β signaling, FOXO signaling, mTOR signaling, oxidative phosphorylation, citrate cycle, alanine, aspartate, and glutamate metabolism, arginine biosynthesis, and valine, leucine, and isoleucine degradation. The identified DEPs and their regulated pathways were involved in regulating intramuscular fat deposition, protein metabolism, and amino acid metabolism in donkey muscles. These mechanisms have a direct impact on the physicochemical properties and flavor of donkey meat. Our findings contribute to a better understanding of the molecular processes influencing the quality of donkey meat. Additionally, the findings of our study may be influenced by the sample size. Therefore, further research with a larger sample is needed to provide a more comprehensive evaluation of meat quality.